"Verteilungs(un)gleichgewicht" in Deutschland: Zweieinhalb theoretische Konzepte und fünf empirische Belege. Gerold Blümle zum 75. Geburtstag - Friedrich L. Sell; Felix Stratmann (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2012)
– In this paper, we defend the idea of the potential existence of equilibrium in personal income distribution in Germany. This concept can be motivated by two different approaches: One is a status theory put forward by Gerold Blümle, the other is a sort of hybrid variant of the prospect theory, put forward by the authors. In both models, the actual size and the distribution of personal incomes are compared with the judgments/beliefs of economic agents about these facts. If agents feel their incomes to be by and large in shape and the income distribution to be fair, then equilibrium is possible. In the second part of the paper, we come up with empirical findings from Germany in the last two decades: since the new millennium income distribution became definitely more unequal and the lower and the medium incomes decreased or at least stagnated. The economic agents involved in this development revealed their feelings in inquiries: a great majority thinks that these changes were inappropriate and unfair. It remains to be seen whether economic policy is willing and/or capable to restore equilibrium in personal income distribution.
Keywords: C44; C81; C82; D31; D63; 330; Theorie und Empirie der personellen Einkommensverteilung; Statustheorie; Prospect-Theorie; Zufriedenheits- und Gerechtigkeitsforschung